Effect of Heat Treatment on Performance of 2205 Base Equipment and Pipes - Yajun Li; Nan Liu; Li Tian; Xuemei Lu; Yanjiao Li (Engineering Reports)
ABSTRACT 2205 dual‐phase stainless steel is widely used in petrochemical equipment. This paper simulates welding, post‐weld heat treatment, and operation conditions of 2205 steel. Microstructure evolution and properties were analyzed via metallography, impact testing, SEM, EDS, and electrochemical methods. Results showed microstructure degradation after 580°C heat treatment, with precipitate formation causing toughness loss. Precipitate diameter was ˜38 nm. Critical corrosion temperature and pitting resistance decreased with increasing heat treatment temperature. It is suggested that 2205 dual‐phase stainless steel should avoid post‐welding heat treatment during the fabricating process. For 2205 dual‐phase stainless steel equipment or parts that must or have completed post‐welding heat treatment, the risk assessment should be carried out based on the service temperature, etc. If necessary, solution treatment should be carried out to maximize the recovery of material properties.